Ca lâm sàng sửa van hai lá qua đường ống thông - Phạm Mạnh Hùng; Nguyễn Ngọc Quang; Nguyễn Thị Thu Hoài; Đinh Huỳnh Linh; Đỗ Doãn Lợi (Tạp chí Tim mạch học Việt Nam, 2015)
Ca lâm sàng sửa van hai lá qua đường ống thông